2016
DOI: 10.2500/ajra.2016.30.4372
|View full text |Cite
|
Sign up to set email alerts
|

Topical Probiotics as a Therapeutic Alternative for Chronic Rhinosinusitis: A Preclinical Proof of Concept

Abstract: We identified well-tolerated, nonpathogenic, "generally recognized as safe" status gram-positive probiotics with anti-inflammatory properties. Topical probiotics represented a potential novel topical therapeutic strategy for CRS relevant for further clinical evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 25 publications
1
28
0
1
Order By: Relevance
“…In another study, Bifidobacterium lactis AD011 increased the production of IL‐10 in a co‐culture with DCs and IECs, whereas L. casei IBS041 and Lactobacillus acidophilus AD031 increased TGF‐β secretion in this co‐culture system . Similar results were obtained in another co‐culture system containing peripheral blood mononuclear cells and L. lactis , that is, an increased secretion of the anti‐inflammatory cytokine IL‐10 . The in vitro data are further supported by in vivo studies in mouse models of allergic airway disease.…”
Section: Probiotic Interactions With the Immune Systemsupporting
confidence: 66%
“…In another study, Bifidobacterium lactis AD011 increased the production of IL‐10 in a co‐culture with DCs and IECs, whereas L. casei IBS041 and Lactobacillus acidophilus AD031 increased TGF‐β secretion in this co‐culture system . Similar results were obtained in another co‐culture system containing peripheral blood mononuclear cells and L. lactis , that is, an increased secretion of the anti‐inflammatory cytokine IL‐10 . The in vitro data are further supported by in vivo studies in mouse models of allergic airway disease.…”
Section: Probiotic Interactions With the Immune Systemsupporting
confidence: 66%
“…To complicate matters further some species may act as commensal under certain circumstances, for example in low abundance or in concert with other microbes, where under different circumstance the same species may induce an inflammatory response. This seems to be the case with S. Aureus where in low abundance it may act as a commensal (Schwartz et al, 2016 ). Our own experiments confirm that certain strains of Propionibacterium , may act as a commensal, but under certain circumstances enhance the growth of pathogens (unpublished data).…”
Section: The Role Of the Commensal Microbiome In The Upper Airwaymentioning
confidence: 99%
“…In 2018, Cervin analyzed probiotics as treatment of chronic sinus infections and pointed out that, although the potential of probiotics has been shown in vitro and in other studies (Table ), it had yet not shown clinical benefit or efficacy in CRS. Further studies were recommended focusing on empirical trials in well‐defined CRS in advance of detailing the underlying mechanism.…”
Section: Resultsmentioning
confidence: 99%